2011
DOI: 10.1111/j.1528-1167.2011.03295.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FDG-PET/MRI coregistration in nonlesional refractory childhood epilepsy

Abstract: SUMMARYPurpose: To validate the use of 18F-fluorodeoxyglucosepositron emission tomography/magnetic resonance imaging (FDG-PET/MRI) coregistration for epileptogenic zone detection in children with MRI nonlesional refractory epilepsy and to assess its ability to guide a second interpretation of the MRI studies. Methods: Thirty-one children with refractory epilepsy whose MRI results were nonlesional were included prospectively. All patients underwent presurgical evaluation following the standard protocol of our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 31 publications
3
59
0
3
Order By: Relevance
“…However, 37 retrospective studies 44 and three prospective studies [45][46][47] were identified to be relevant to this systematic review (Figure 1). Six of these studies were reported solely in abstract form, 17,24,25,34,38,41 whereas two studies 30,33 had both the full publication and the abstract. Because of the heterogeneity of the studies in the patient population, study design, outcome measurements, and methods of PET interpretation, the results of the studies included in the systematic review could not be pooled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 37 retrospective studies 44 and three prospective studies [45][46][47] were identified to be relevant to this systematic review (Figure 1). Six of these studies were reported solely in abstract form, 17,24,25,34,38,41 whereas two studies 30,33 had both the full publication and the abstract. Because of the heterogeneity of the studies in the patient population, study design, outcome measurements, and methods of PET interpretation, the results of the studies included in the systematic review could not be pooled.…”
Section: Resultsmentioning
confidence: 99%
“…In this same cohort, surgical resection guided by PET/MRI coregistration and electrocorticography resulted in 82% of the patients achieving seizure freedom. In another retrospective study involving children with refractory epilepsy, 30 PET/MRI coregistration guided the second MRI interpretation from nonlesional to subtle lesional in 42% of the cases. Similarly, PET/ MRI coregistration was able to detect Taylor-type focal cortical dysplasia in patients with negative MRI and where a PET scan alone does not allow a conclusive diagnosis.…”
Section: F-fdg Pet/mri Coregistrationmentioning
confidence: 99%
“…Because somatostatin receptors (especially subtype 2) are expressed on the surface of some neuroblastomas, radiolabeled somatostatin analogs such as 68 Ga-and 177 Lu-octreotide may be beneficial for imaging and targeted radiotherapy, especially for primary refractory or relapsed high-risk neuroblastomas (52). Given the higher sensitivity and better spatial resolution of somatostatin receptor PET than of somatostatin receptor scintigraphy for detecting somatostatin receptor-positive tumor lesions, combined PET/MR may be advantageous, especially for small liver lesions.…”
Section: Soft-tissue Tumorsmentioning
confidence: 99%
“…This may reflect the difficulty in localizing and resecting the epileptogenic zone [60]. In order to improve the radiographic detection of epileptogenic lesions, more advanced imaging techniques have been used such as 7T MRI, volumetric analysis, Diffusion Tensor Imaging (DTI), arterial spin labeling and PET [38,[66][67][68][69][70][71][72][73][74]. However, it is currently unknown if such techniques willimprove outcomes.…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Anti-NMDA antibody, Anti-GABAB antibody, Anti-AMPA antibody, Anti-LGI1 antibody, Anti-CASPR2 antibody, Anti-contactin-2 antibody, Anti-GAD antibody, Anti-VGKC antibody [32][33][34][35][36][37][38].…”
Section: Autoimmune Epilepsiesmentioning
confidence: 99%